Investigating the Impact of Political Stability, Trade Liberalization, and Investment Incentives on the FDI Inflows in Pakistan - Akram, Affaq (South Asian Review of Business and Administrative Studies (SABAS), 2020)
This study examines the impact of the political stability and trade openness, trade liberalization and investment incentives on the FDI Inflow of Pakistan. FDI in all over the world has been growing at a spectacular pace and Pakistan as an emerging economy has been successful in attracting more FDI compared to developed countries. The data for this study were collected through the World Bank (World Bank Indicator Database) and The Global Economy from the period of 1995-2018. The procedure of ARDL bound testing was applied to observe the association between FDI and political stability alongside other indicators such as trade openness, and incentives to investments in Pakistan. Tests were carried out to observe short-run and long-run relationships. FDI inflow were found to be significantly and positively influenced by trade openness and incentives in the long run. For the policymakers, the implications in our research underlie improvements to political establishments and a stable democratic system along with investor’s friendly long term policies that are central to attracting more FDI in Pakistan. Moreover, the Government should focus on removing uncertainties which lead to instabilities. Stable government may manage credible trade reforms to further liberalize its trade to enhance FDI inflows and reduce tariffs with the motive of providing incentives on investments..